Factors underlying bus-related crashes in Hanoi, Vietnam - La, Quong Ngoc; Duong, Dat Van; Lee, Andy; Meuleners, Lynn (Pergamon, 2017)
Road traffic crashes accounted for almost 13% of the total mortality recorded at the public health facilities in Vietnam in 2010. This qualitative study investigated factors related to bus-related crashes in Hanoi, Vietnam using focus group discussions and in-depth interviews among 75 participants who are bus drivers, motorcycle users, bus passengers, bus company managers, traffic policemen and local authorities. The results suggested that bus drivers were not the sole contributor to road traffic crashes with other vehicles. The rapid population growth due to rural to urban migration and the poor transport system appeared to be important contributing factors. In addition, "village culture" was likely to influence both the traffic behaviors of road users and the practices of law enforcement officers. Moreover, drink-driving behaviors appeared to be an important contributor to bus-related crashes. Supervision and penalty policies of bus companies also appeared to influence the driving performance of bus drivers. For a long-term solution to reduce bus-related crashes, it is vital to improve the transport infrastructure and the state management capacity regarding road safety as well as to assist the positive transition of citizens migrating from rural areas to their new urban lifestyle.